PERBANDINGAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN METODE PEMBELAJARAN MIND MAPPING DAN DIRECT INSTRUCTION PADA SISWA KELAS V SDN JIWAN 01 MADIUN - Prima Rias Wana, Widya Trio Pangestu, Degi Alrinda Agustina (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Abstract: This study aimed to compare mathematics learning achievement of students with Mind Mapping learning methods and mathematics achievement of students with direct instruction methods. This research is a quantitative study using an experimental method. This study population is the class V SDN Jiwan 01. The sample consists of two classes, namely class V A total of 30 students by Mind Mapping learning methods and class V B as many as 29 students by direct instruction method. Data taken using the test method. Data analysis using t test. The results of data analysis showed that the average value of the class by direct instruction methods is 53.611 while the average grade by Mind Mapping learning methods is 62.121. Results of t-test showed that the achievement tobs= 2,449 with a significance level of 5% and dk=68 obtained ttabel = 1,645. tobs > ttabel. This means that H0 is rejected. Thus the working hypothesis proposed by the researchers rejected. So student achievement taught using Mind Mapping method of learning is better than learning achievement of students who are taught by the direct instruction method.